Digital Communication of ‘Aisyiyah during the COVID-19 Pandemic - Dika Nanda Kinanti; Putut Widjanarko (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2023)
The widespread penetration of digital communication, especially social media, in every aspect of life, provides a means for the women's movement to increase women’s empowerment. 'Aisyiyah, one of Indonesia's largest women's organizations, has also started using social media platforms. Therefore, this research aims to find out how digital communication is used by 'Aisyiyah to promote women's awareness of the issues they face, build the 'Aisyiyah movement's public identity, and mobilize collective actions. This single-instrumental case study research was conducted during the COVID-19 pandemic when digital communication became much more important due to restrictions on mobility and offline meetings. Data was collected through semi-structured interviews with Aisyiyah's media team and document reviews of its official social media accounts (Instagram and YouTube). This research shows that 'Aisyiyah has started to use a digital storytelling perspective in empowerment initiatives related to women's issues (such as reproductive health, violence against women, and the economy). In addition, strengthening the organization's identity in public becomes a significant theme in 'Aisyiyah's digital communication. Thus, digital communication efforts for collective action should catch up, indicating, in general, that women's movements, especially in Indonesia, still need to form a networked social movement.